The invincible summer of Juniper Jones - McQueen, Daven (Wattpad Books, 2020)
In 1955, biracial Ethan, who was raised in Washington state, is sent to live with his grandparents in Alabama for the summer. Ethan's eyes are opened to blatant racism for the first time, but also to kindness, when a young red-head named Juniper Jones befriends him and they spend the summer exploring the town and having adventures. Their friendship becomes a lifeline for Ethan when the town's ugliness turns deadly.